The contribution of turmeric research and development In the economy of Bangladesh: an ex-post analysis (International Journal of Agricultural Research, Innovation and Technology, 2014)
The study estimated the benefit and rates of returns to investment on turmeric research and development in Bangladesh. The Economic Surplus Model with ex-post analysis was used to determine the returns to investment and their distribution between the production and consumption. Several discounting techniques were also used to assess the efficiency of turmeric research. The adoption rate was found increasing trend over the period. The yield of BARI developed modern varieties of turmeric was 41 to 73% higher than those of the local variety. Society got net benefit Tk. 9333.88 million from the investment of turmeric research and extension. The net present value (NPV) and present value of research cost (PVRC) were estimated at Tk. 1200.84 and 157.88, respectively. The internal rate of return (IRR) and benefit cost ratio (BCR) were estimated to be 68% and 10.45, respectively indicated investment on turmeric research and development was a good and profitable investment. Seed production programme of turmeric should be taken largely to increase production by increasing area adoption. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.20968 Int. J. Agril. Res. Innov. & Tech. 4 (1): 1-10, June, 2014